Malaysian regulators’ ranking of PPP contract governance skills - Abdullahi, Ahmed Umar; Noor Amila, Wan Abdullah Zawawi; Abdul Rashid, Abdul Aziz (Emerald Publishing Limited, 2020)
Purpose–The purpose of this study is to explore the skills required by regulatory agencies for effectivegovernance of public-private partnership (PPP) contracts from the perspective of Malaysian regulators. Thereis a growing literature indicating that there is poor public sector expertise in managing PPP projects.Design/methodology/approach–The study, being an exploratory one, relied on a questionnaire survey ofthe Malaysian PPP unit (UKAS) and five Malaysian regulatory agencies responsible for regulating servicedelivery across a number of sectors.Findings–The results of the exploratory factor analysis returned six factor groupings, indicating that themost important skills are procurement, auditing and forensic accounting, lifecycle costing, sector-specific,negotiation analysis and performance management. It was also found that academic qualifications, profession,years of experience and the regulatory agency had no mediating effect on the rankings.Practical implications–The findings show that infrastructure regulation training programs should betailored to reflect regional and country-specific characteristics. This is because a similar study with a globalisedset of respondents gave a different result from the current study.Originality/value–There is a growing trend towards remunicipalisations and contract cancellationsglobally. This is the very outcome that regulatory agencies were created to prevent. Studies includinggovernment reports are increasingly pointing in the direction of poor skills set among public sector staffmanaging PPPs. This lack of capacity has resulted in poor oversight, which now threatens the sustainability ofservice provision.